The Effect of Organizational Culture, Anti-Fraud Awareness on Fraud Prevention with the Effectiveness of the Whistleblowing System as a Moderating Variable - Dian Melisa; Yona Octaviani Bela (Yayasan Az Zukhruf Cendikia, 2025)
Purpose - This research aims to obtain empirical evidence about the effect of organizational culture, anti-fraud awareness on fraud prevention with the effectiveness of the whistleblowing system as a moderating variable. Design/methodology/approach - This research uses quantitative research. This research was conducted using a questionnaire distributed to all individuals who work in the government sector (Dinas Kopersi Usaha,Kecil dan Menengah Kota Bekasi). 65 questionnaires were distributed via Whatsapp social media. Each questionnaire distributed contained 38 statements to be answered by respondents. From the distribution of questionnaires carried out, 30 respondents who provided answers were obtained from the Dinas Kopersi Usaha,Kecil dan Menengah Kota Bekasi. To get the results of this study, researchers used PLS SEM Version 3.0. Findings - The results of this study found that Organizational Culture has a positive effect and has no significant effect on fraud prevention, Anti-Fraud Awareness has a positive effect and has no significant effect on fraud prevention, the effectiveness of the whistleblowing system can strengthen the relationship between organizational culture and fraud prevention, the effectiveness of the whistleblowing system can strengthen the relationship between anti-fraud awareness and fraud prevention. Originality / value - This research focuses on fraud prevention, where this research is a new research in discussing the relationship between Organizational Culture, Anti-Fraud Awareness and the Effectiveness of the Whistleblowing system.